The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jonm.13153
|View full text |Cite
|
Sign up to set email alerts
|

The association between supervisor support and ethical dilemmas on Nurses' intention to leave: The mediating role of the meaning of work

Abstract: Aim To examine the association between supervisor support and ethical dilemmas on nurses' intention to leave health care organisations, both directly and through the mediating role of the meaning of work. Background The shortage of nurses makes it vital that organisations retain nurses and so reduce the costs associated with replacing experienced nurses. Methods This cross‐sectional study samples 2,946 registered nurses from a selected health region in Norway. Structural equation modelling was used to test a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…The global nursing shortage was a well‐recognized and well‐researched issue before the pandemic (Canadian Nurses Association [CNA] and Registered Nurses Association Ontario [RNAO], 2010 ; International Council of Nurses [ICN], 2021 ; Labrague & De los Santos, 2020 ), and there are now signs that the pandemic may be worsening this situation (Berlin et al, 2021 ). Furthermore, this long‐standing global public health crisis has only served to exacerbate the chronic issues the nursing workforce has faced in the past few decades such as high amounts of turnover, absenteeism, sick leaves and heavy workloads and unsafe patient ratios (CNA and RNAO, 2010 ; Hognestad Haaland et al, 2020 ; Moloney et al, 2018 ; Van der Heijden et al, 2019 ). Using the JD‐R model (Bakker et al, 2008 ) as a conceptual framework, the present study argued that caring for COVID‐19 patients during the pandemic is an important job demand that is likely to increase nursing staff's strain (e.g., chronic fatigue and low work satisfaction) and impact their performance in terms of quality of care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The global nursing shortage was a well‐recognized and well‐researched issue before the pandemic (Canadian Nurses Association [CNA] and Registered Nurses Association Ontario [RNAO], 2010 ; International Council of Nurses [ICN], 2021 ; Labrague & De los Santos, 2020 ), and there are now signs that the pandemic may be worsening this situation (Berlin et al, 2021 ). Furthermore, this long‐standing global public health crisis has only served to exacerbate the chronic issues the nursing workforce has faced in the past few decades such as high amounts of turnover, absenteeism, sick leaves and heavy workloads and unsafe patient ratios (CNA and RNAO, 2010 ; Hognestad Haaland et al, 2020 ; Moloney et al, 2018 ; Van der Heijden et al, 2019 ). Using the JD‐R model (Bakker et al, 2008 ) as a conceptual framework, the present study argued that caring for COVID‐19 patients during the pandemic is an important job demand that is likely to increase nursing staff's strain (e.g., chronic fatigue and low work satisfaction) and impact their performance in terms of quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of job demands and job resources on quality of care and nurses' chronic fatigue has also been demonstrated (e.g., LeGal et al, 2019 ; Van Bogaert et al, 2018 ). Furthermore, a number of nursing demands and resources, or lack of resources, and the resulting high strain have been associated with intentions to leave the work setting and/or profession (e.g., Hognestad Haaland et al, 2020 ; Moloney et al, 2018 ; Van der Heijden et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong supervisor support directly decreases withdrawal cognitions (Maertz et al, 2007) and likely plays a prominent role in mitigating the negative relationship between satisfaction and turnover. Indeed, nurses who perceive their supervisors are supportive are more engaged (Othman & Nasurdin, 2013) and less likely to quit the organisation (Haaland et al, 2020). COR theory suggests supervisor support provides tangible and intangible resources, which instrumentally refuel depleted resources, and mitigates the relationship between dissatisfaction and turnover intent.…”
Section: The Moderating Role Of Supervisor Supportmentioning
confidence: 99%
“…Regarding turnover intentions, relationships have been found with lower relation-oriented leadership, younger age (Fontes et al, 2019), being male (Sasso et al, 2019), burnout or emotional exhaustion (Lee et al, 2020;Sasso et al, 2019), and ethical dilemmas (Hognestad Haaland et al, 2021). Factors found to decrease turnover intentions are good nurse-physician relationship, leadership (Sasso et al, 2019), supervisor support (Hognestad Haaland et al, 2021), work engagement (Wan et al, 2018), meaning of work (Hognestad Haaland et al, 2021), participation in hospital affairs, high job satisfaction, personal accomplishment (Sasso et al, 2019), organizational commitment, higher educational level (Lee et al, 2020) and supportive work practice environment (Lee et al, 2020;Wan et al, 2018). A study of intention to leave the profession in 10 European countries found the following relationships: lower odds for good nursephysician relationships, leadership, participation in hospital affairs, working full time, and female gender and higher odds for older age and burnout (Heinen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%